Group composition effects on inter-pack aggressive interactions of gray wolves in Yellowstone National Park - Cassidy, Kira A. (2013)
University of Minnesota M.S. thesis. September 2013. Major: Natural Resources Science and Management. Advisor: Dr. L. David Mech. 1 computer file (PDF); vi, 51 pages, appendices p. 46-51. Gray wolves (Canis lupus) are group-living carnivores that defend group territories and direct aggression against conspecifics. Here, I document 292 inter-pack aggressive interactions during 16 years of observation in Yellowstone National Park (YNP). I recorded pack sizes, compositions, and spatial orientations related to residency to determine their effects on the outcomes of aggressive interactions between groups. This represents the first attempt at directly observing aggressive interactions over an extended period and subsequently using pack characteristics to determine which groups had an advantage over their opponents. Relative pack size (RPS) was the most important factor in the odds of a pack being able to successfully displace their opponent. However, when RPS was fixed, packs with more old (>6.0 years old) members or with more adult males also had higher odds of winning. I discuss these results with respect to the adaptive value of sociality and the relative importance of certain individuals during inter-group interactions. While the importance of RPS in successful resource- and territory-defense suggests the evolution and maintenance of group-living may be due to larger packs' success during inter-pack interactions, group composition--which can change irrespective of group size--is also an important factor highlighting that some individuals are more valuable than others during inter-pack conflicts.